Effect of Prenatal T4 Treatment in Neonatal Morbidity: Preliminary Findings - Reyes, Gloria; Romaguera, Josefina; Zapata, Rafael; Valcarcel, Marta; Adamsons, Karlis (Puerto Rico Health Sciences Journal, 2025)
see manuscript